EFEKTIVITAS OBAT ANTIBIOTIK UNTUK DEMAM TIFOID TERHADAP PASIEN ANAK DI RUMAH SAKIT UMUM DAERAH dr. AGOESDJAM KABUPATEN KETAPANG KALIMANTAN BARAT PERIODE 2019 - Wardati, Yulia (Prodi Farmasi - Universitas Al Ghifari, 2024)
Typhoid fever is the third of the 10 main diseases in patients treated in hospitals in Indonesia, while at RSUD dr. Agoesdjam West Kalimantan is ranked fourth. The aim of the research is to determine patterns of drug use and evaluate the effectiveness of antibiotic drugs for patients with thiophid fever at RSUD dr. Agoesdjam. This research is an observational study with retrospective data collection in May-July 2019, with a total of 103 patients. The inclusion criteria taken were medical record data from patients aged 5 to 10 years, who were diagnosed with typhoid fever at the inpatient installation of the Regional General Hospital ( RSUD) Dr. Agoesdjam Ketapang, West Kalimantan. Exclusion criteria are; Medical records for typhoid fever patients have other comorbidities such as kidney failure, psychiatric disorders, and so on.The parameters for the effectiveness of the drugs used are LoS, LoSAR, reduction in body temperature and reduction in the number of leukocytes. The results obtained were the use of antibiotics including chloramphenicol, ampicillin, ceftriaxone and cefixime. Based on LoS parameters, ceftriaxone was the most effective (2.77 days), LoSAR ceftriaxone (5 days), decreased body temperature ampislin (4.2 °C) and decreased leukocytes ampislin (6075 cells per micro liter). The most antibiotic used was chloramphenicol (41 patients). The most effective drugs were ceftriaxone (according to LoS and LoSAR parameters) and ampicillin (according to body temperature and leukocyte reduction parameters).